ICH Entrepreneurship Opportunties via Halal Sustainability Audit and ISO 53002 for 2030 - Yeung, Shirley Mo Ching (Journal of Ecohumanism, 2025)
The application of Halal concepts to the ICH, for example, cheongsam market for 2030 presents a compelling opportunity for growth. By understanding Halal audit system with ISO PDCA System - ethical sourcing and planning, doing in production of products/ services, and checking with design review, and acting with integrating AI for audit review and continual improvement with the inherent sustainability of traditional cheongsam craftsmanship and the principles of Halal audit system and relevant ISO standards, S.E. countries can create a market that may create decent jobs (SDG#8) and nurture a mindset of SDG#3/12/16 culturally rich, ethically sound, and truly sustainable with peace. Based on nvivo analysis of 30 research papers related to halal sustainability system, the key elements for competent halal sustainability audit talents are: 1) system with policy, 2) process with segregation, 3) understanding of Islamic Law, and 4) socialization without misleading messages. This requires a conscious effort to bridge cultural understanding, embrace ethical practices, and leverage the power of tradition and innovation to groom future entrepreneurs in ICH with cultural beauty and halal responsibility.